Evidence for the third stellar population in the Milky Way's disk - Carollo, Daniela; Chiba, Masashi; Battistini, Chiara (The astrophysical journal, 2019)
The Milky Way is a unique laboratory in which stellar properties can be measured and analyzed in detail. In particular, stars in the older populations encode information on the mechanisms that led to the formation of our Galaxy. In this article, we analyze the kinematics, spatial distribution, and chemistry of a large number of stars in the solar neighborhood, where all of the main Galactic components are well represented. We find that the thick disk comprises two distinct and overlapping stellar populations with different kinematic properties and chemical compositions. The metal-weak thick disk (MWTD) contains two-times less metal content than the canonical thick disk, and exhibits enrichment of light elements typical of the oldest stellar populations of the Galaxy. The rotational velocity of the MWTD around the Galactic center is ∼150 km s−1, corresponding to a rotational lag of 30 km s−1 relative to the canonical thick disk (∼180 km s−1), with a velocity dispersion of 60 km s−1. This stellar population likely originated from the merger of a dwarf galaxy during the early phases of our Galaxy’s assembly, or it is a precursor disk, formed in the inner Galaxy and brought into the solar neighborhood by bar instability or spiral-arm formation mechanisms.
Gesehen am 10.02.2020